2001
DOI: 10.1038/sj.ijir.3900719
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and sexual function

Abstract: The use of the D 1 =D 2 dopamine receptor agonist apomorphine SL for the treatment of erectile dysfunction provides a strong support in favour of a participation of the dopaminergic system in the control of sexual function. However, the exact involvement of dopamine in sexual motivation and in the control of genital arousal in humans is unknown. In contrast, experimental data suggest an implication of dopamine at all these stages of the copulatory behaviour in rodents. The release of dopamine at the level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 36 publications
0
39
0
1
Order By: Relevance
“…The responsiveness of dopaminergic systems has been coupled as a predictor of social status in cynomolgus monkeys (Macaca fascicularis) (Morgan et al 2000). Dopamine is also involved in regulating feeding and reproductive motivation (Giuliano and Allard 2001;Terry et al 1995) and appears to influence the motivated stereotypical agonistic behavior in Anolis and the memory of aggressive interaction ). Motivation to react may be viewed as a threshold effect.…”
Section: Introductionmentioning
confidence: 98%
“…The responsiveness of dopaminergic systems has been coupled as a predictor of social status in cynomolgus monkeys (Macaca fascicularis) (Morgan et al 2000). Dopamine is also involved in regulating feeding and reproductive motivation (Giuliano and Allard 2001;Terry et al 1995) and appears to influence the motivated stereotypical agonistic behavior in Anolis and the memory of aggressive interaction ). Motivation to react may be viewed as a threshold effect.…”
Section: Introductionmentioning
confidence: 98%
“…Consistent with this finding, dopamine antagonists have been shown to worsen or elicit RLS symptoms [3,4]. The central dopaminergic system also plays a major role in the control of sexual functions [5]. Studies related to this subject have shown that dopamine in the hypothalamus (particularly the medial preoptic area) plays a role in regulating sexual behaviors via determining the strength of libido, arousal and erection [6].…”
Section: Introductionmentioning
confidence: 88%
“…Decreased dopamine activity known to depress mood can also depress sexual function. 61 It has also been shown that endothelial cells synthesize and release dopamine, and they do so in response to ischemia. 62 This causes a shortage of oxygen and glucose needed for cellular metabolism.…”
Section: Depression Cardiovascular Disease and Erectile Dysfunctionmentioning
confidence: 98%